Phosphatidylethanolamine at the Luminal Endothelial Surface—Implications for Hemostasis and Thrombotic Autoimmunity - Zhixin Li; Wells, Clive W.; North, Paula E.; Kumar, Suresh; Duris, Christine B.; McIntyre, John A.; Ming Zhao (Clinical and applied thrombosis/hemostasis, 2011)
Objective: Accumulating evidence suggests that phosphatidylethanolamine (PE) is physically present at the luminal endothelial surface, where it tentatively functions as a critical anticoagulant. The goal of the current investigation was 3-fold: to characterize the distribution profile of PE at the luminal endothelial surface; to examine the immunoreactivity to the vascular endothelium by anti-PE (aPE) sera from patients presenting with thrombosis; and to discuss the potential mechanism of PE upregulation by endothelial cells. Methods: The rat aortic arch was selected as major conduit vessel under significant hemodynamic burden. The presence of PE and the antigenic profile of aPE sera at the luminal endothelial surface were examined using duramycin as a PEbinding probe and immunohistochemistry. Phosphatidylethanolamine upregulation at endothelial cell surface was investigated using cultured monolayer subject to laminar shear stress or thrombin treatment. Results: High levels of PE were detected at the luminal endothelial surface of aortic flow dividers, the ascending aorta, and the outer curvature of the aortic arch. The antigenic profiles of aPE sera, which are highly associated with elevated thrombotic risks in patients, are consistent with PE distribution along the endothelial surface. Finally, PE is upregulated at the surface of cultured endothelial cells in response to luminal shear stress but not thrombin. Conclusions: The current data describe the physical distribution of vascular PE at the blood—endothelium interface. The luminal PE presents a vulnerability to anti-PE autoimmunity and is consistent with the association between aPE and elevated risk for idiopathic thrombosis.